Simple code lock / Fariz Masrizal Mostafa and Khairul Azwan Abd Rahman - Mostafa, Fariz Masrizal; Abd Rahman, Khairul Azwan (2006)
Final project is a part of a course structure for the student in their final year. The project is compulsory to us as a final year student for Dip. In. Electrical Engineering. The purpose of project is to produces a student a main power with high skill and able to handle a responsibility given like a project. They should prepared to deliver a creative ideas and good interpersonal image to their future employer . It make student used all of their knowledge .creative and skills to propose , create , and trouble shoots the projects. It is because all of the theories and have learned from the project one to project two are used. This project have is of an electronic combination lock for daily use. It response only to the right sequence of our digital that are keyed in remotely. If a wrong keyed is touched it reset the locks. This circuit project can divide into three sections. First section is switch line, second section is integrated circuit and last section is relay as an output. For example of this operation, we can locks at the door lock. First we push the correct code or codeword to the lock number. Then if the right code is push, the door will open, otherwise if the wrong keyed is touched, the door will not open and the siren will be sactived. Another example, this circuit can be usefully employed in cars so that only when the correct code sequence is keyed in via the pad. This circuit can also be used in various other applications, our devices can be usefully employed as safety system.